Peningkatan Kinerja UKM: Peran Keunggulan Bersaing dalam Memoderasi Pengetahuan Produk dan Literasi Keuangan - Yuliana, Ika; Alpiansah, Restu; Rahmatullah, Arwin Yafi; Dethan, Stevany Hanalyna (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Small and Medium Enterprises (SMEs) are essential drivers of Indonesia’s economic development, particularly in the informal sector. Despite their potential, food-based SMEs in Mataram continue to face challenges in sustaining competitive performance. This study aims to examine the effect of product knowledge and financial literacy on SME performance, with a specific focus on the moderating role of competitive advantage. The study adopts a quantitative approach using the Partial Least Squares (PLS) analysis method. A purposive sampling technique was employed, involving 160 food SME owners or managers in Mataram, Lombok, who have been operating for at least six months. Measurement validity was confirmed through outer loadings and AVE values, while hypothesis testing involved direct and moderating effects. The results show that both product knowledge and financial literacy have a significant and positive influence on SME performance. Product knowledge enhances marketing confidence, while financial literacy supports efficient resource management. Furthermore, competitive advantage significantly moderates the relationship between product knowledge and performance, reinforcing its effect. However, it does not significantly moderate the relationship between financial literacy and performance, suggesting that without a well-managed strategic edge, financial literacy alone cannot optimize performance outcomes. These findings underline the importance of integrating knowledge, financial acumen, and a sustained competitive advantage to achieve superior and sustainable SME performance. This study offers valuable practical insights for SME actors to strengthen strategic capabilities and contribute to regional economic resilience.